Implementation of the Use of "GPS: Hazard Map" in the Implementation of Patrol to Prevent Cases of Theft by Weighting at Jombang Police - Kusumawardani, Putri Hellyana (Indonesian Journal of Police Studies, 2024)
In this case, the Samapta Unit of Jombang Police carried out preventive actions aimed at improving security and order in the Jombang Police community by implementing patrols carried out by the Samapta Unit of Jombang Police using the “GPS : Map Of Vulnerability” system. The purpose of implementing patrol activities using the help of “GPS: Map Of Vulnerability” is one form of effort made by the police as a form of implementing patrols with areas that have been determined based on reports on the level of vulnerability of an area. Based on the results of the research conducted, researchers can implement patrols using the “GPS: Map of Vulnerability” system as a tool in patrol activities to maintain security and order for the people of Jombang Regency. There are several new findings that can be used as evaluation material related to planning, organizing, implementing and supervising the implementation of patrols using the help of GPS: Map of Vulnerability. The weaknesses, shortcomings, opportunities and threats to the tools used in the implementation of patrols.